Analisis Kualitas Perangkat Lunak Sistem Informasi Perpustakaan Sekolah Menggunakan Metode Black Box Testing Berbasis Standar ISO/IEC 29119 - Kamila Salma Sofyan; Sheni Febriyanti; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
The implementation of information technology in school libraries aims to enhance the efficiency of member data management and book circulation. However, vulnerabilities in system logic often lead to fatal inventory data inaccuracies. This study aims to validate the functionality of a web-based library application by applying the Black Box Testing method. The testing stages are structured according to the ISO/IEC 29119 international standard, covering planning, design, and test execution. Test case design techniques utilize Equivalence Partitioning and Boundary Value Analysis to test input validation limits and business logic. Testing was conducted on 27 test cases covering authentication modules, master data management (students and books), and loan transactions. The results showed that out of a total of 27 test cases, 21 cases were declared successful (Pass) and 6 cases failed (Fail). Bug findings included critical categories where the system allowed borrowing on zero stock causing negative values, return date logic errors, and the absence of validation on student data input forms. In conclusion, while the basic features of the application are operational, significant improvements in back-end validation and stock algorithm logic are required before the system is released to the production environment to ensure data integrity.